The early diagnostic value of neutrophil to lymphocyte ratio and platelet to lymphocyte ratio in neonatal late-onset sepsis - Yin, Qigai; Yin, Jing; Shen, Lu; Zhou, Qin; Xu, WeiDong (Frontiers in Pediatrics, 2025)
PurposeThe purpose of this study is to investigate the early diagnostic value of the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and C-reactive protein (CRP) in neonatal late-onset sepsis (LOS), as well as to evaluate the combined diagnostic utility of these markers for the early detection of neonatal LOS.MethodsThe late-onset sepsis of newborns admitted to the neonatal intensive care unit of our hospital were retrospectively collected. 142 children with Late-Onset Sepsis (LOS) were selected as the LOS group, 50 neonates with systemic infection were selected as the systemic infection group, 50 neonates who underwent physical examination were selected as the non-systemic infection group. The differences of NLR, PLR, platelet-to-neutrophil ratio (PNR), and C-reactive protein (CRP), Procalcitonin among the three groups were compared.ResultsThe levels of NLR and PLR in LOS group were significantly higher than those in systemic infection group and non-systemic infection group. The Receiver Operating Characteristic (ROC) curve result revealed that the area under ROC (AUC, Area Under Curve) of NLR for the diagnosis of LOS was 0.903. When the optimal cut-off value was 1.30, the sensitivity and specificity were 89.4% and 81.0%. The AUC of PLR for the diagnosis of LOS was 0.833. When the optimal truncation value was 57.86, the sensitivity and specificity were 92.3% and 68.0%. The AUC of CRP for the diagnosis of LOS was 0.876, and the sensitivity and specificity were 76.8% and 87.0% when the optimal cut-off value was 10.21 mg/dl. When NLR, PLR, and CRP were combined to diagnosis LOS, The AUC was 0.942, the sensitivity and specificity were 90.8% and 86.0%.ConclusionsThe levels of NLR and PLR in the LOS were higher, which have certain value in the early diagnosis of LOS, and combined with CRP can improve the diagnostic efficiency.